The ebg operon consists of at least two genes. - Hall, B G (1980)
The ebg operon of Escherichia coli includes a second gene designated ebgB. The ebgB gene product is a 79,000-molecular-weight protein and is expressed coordinately with the ebgA gene product, ebg beta-galactosidase. Insertion of the transposable elements Tn5 and Tn9 into ebgA eliminates the expression of ebgB, suggesting that ebgB is distal to ebgA. Ultraviolet light mapping confirms that gene order. The function of the ebgB gene product is unknown.